2005
DOI: 10.1099/jmm.0.45988-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of potential virulence markers in Polish Campylobacter jejuni and Campylobacter coli isolates obtained from hospitalized children and from chicken carcasses

Abstract: The pathogenicity of thermotolerant Campylobacter species, common food-borne pathogens, depends on certain factors unevenly distributed among strains of different origin. The prevalence of such markers has never been examined in a population of Polish Campylobacter strains of human and poultry origin. Therefore, we analysed the presence of the cadF, cdtA, cdtB and cdtC genes and the iam sequence in Campylobacter jejuni (n ¼ 115) and Campylobacter coli (n ¼ 57) isolates from children with diarrhoea and from chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
63
3
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 21 publications
14
63
3
4
Order By: Relevance
“…These results are similar to data previously reported by other authors (Datta et al 2003;Rozynek et al 2005;Krutkiewicz and Klimuszko 2010;Rapabelli et al 2010). The invasion-associated marker (iam) of Campylobacter was another virulence marker detected in this study.…”
Section: Discussionsupporting
confidence: 83%
“…These results are similar to data previously reported by other authors (Datta et al 2003;Rozynek et al 2005;Krutkiewicz and Klimuszko 2010;Rapabelli et al 2010). The invasion-associated marker (iam) of Campylobacter was another virulence marker detected in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Analysis of the cadF gene has revealed its high prevalence (i.e., 100%) among Campylobacter spp. isolates derived from poultry carcasses, broiler faeces, bovine faeces, retail raw meat, pig and cattle, 18,[30][31][32]36 and also among isolates of human origin. 30,31,37 The cadF gene is probably conserved among Campylobacter spp isolates, 18 regardless of their origin or species, as is the case also in the C. coli 26536 isolate used here.…”
Section: Discussionmentioning
confidence: 99%
“…isolates derived from poultry carcasses, broiler faeces, bovine faeces, retail raw meat, pig and cattle, 18,[30][31][32]36 and also among isolates of human origin. 30,31,37 The cadF gene is probably conserved among Campylobacter spp isolates, 18 regardless of their origin or species, as is the case also in the C. coli 26536 isolate used here. In contrast, several studies have shown wide variations for the presence of virB11, which was not found in C. jejuni and C. coli isolates from poultry faeces, 18 although it was identified in 4% to 15% of isolates tested from poultry meat, pig and cattle, 31,32,36 and in 10% to 17% of human clinical samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations